PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY BERBANTUAN ASSEMBLR EDU PADA MATERI PANCASILA DALAM KEHIDUPANKU KELAS V SEKOLAH DASAR - Meiranda Sartika; Diana Pramesti; Rifki Hanif Setiawan (STKIP Subang, 2026)
Based on preliminary observations conducted at SD Negeri 28 Pangkalpinang, teachers were found to experience constraints in developing technology-based instructional media. The demand for learning media was strong in a student-led needs analysis (88.75 percent), suggesting that these tools are indispensable in the classroom. Therefore, the purpose of this study was to create and test augmented reality (AR) learning materials using Assemblr Edu on the subject of